FAKTOR-FAKTOR YANG MEMPENGARUHI NON PERFORMING LOAN - Laudita Duanty, 09.05.52.0125; Suwarti, Titiek (Students Journal of Accounting and Banking, 2013)
The purpose of this study to analyze the factors affecting the Non Performing Loan (NPL). These factors are Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Bank size (size). This study uses secondary data with the source data from the Indonesia Stock Exchange with the period 2008-2011. Sampling was purposive sampling method. Data analysis using classical assumptions, multiple linear regression analysis, the coefficient of determination, F test and t test with CAR, LDR, and size as the independent variable and (NPL) as the dependent variable. The results showed that the variable CAR no significant positive effect on NPL. While variable LDR significant positive effect on NPL. Variable Bank Size no significant negative effect on (NPL).Keywords: Non Performing Loan, Capital Adequacy Ratio, Loan to Deposit Ratio, Size Bank.